A new method of sentinel node mapping for early gastric cancer using a fluorescent laparoscope that can adjust the intensity of excitation light and quantify the intensity of indocyanine green fluorescence: Report of a case. (2020) - Kamada, Teppei; Yoshida, Masashi; Takeuchi, Hideyuki; Narihiro, Satoshi; Ohdaira, Hironori; Suzuki, Yutaka
Highlights: VISION SENSE® is a new near-infrared fluorescence laparoscope, and allows adjustment of the intensity of excitation light and quantification of the intensity of ICG fluorescence during observation. Using VISION SENSE®, when many ICG-positive lymph nodes are observed, we can select lymph nodes by quantifying ICG fluorescence during surgery. This procedure might improve SN mapping for early gastric cancer. Abstract: Introduction: One of the drawbacks of indocyanine green (ICG) fluorescence sentinel node (SN) mapping is the impossibility of quantifying lymph node fluorescence during surgery. VISION SENSE® is a new near-infrared fluorescence laparoscope for bright-field full-color observation, and provides the ability to adjust the intensity of excitation light and quantify the intensity of ICG fluorescence during observation. We report the case of a patient who underwent ICG SN mapping for early gastric cancer using VISION SENSE®. Presentation of case: A woman in her 60 s was diagnosed with cType0-IIc early gastric cancer located in the anterior wall of the middle gastric body (25 mm in diameter, cT1b, cN0, cM0, cStage IA). Contrast-enhanced computed tomography showed no metastases. Laparoscopy assisted distal gastrectomy with D1+ lymph node dissection and SN mapping with ICG fluorescence using the VISION SENSE® were successfully performed. Using VISION SENSE®, we could select those lymph nodes objectively showing high intensity by quantifying ICG fluorescence during surgery. The pathological diagnosis was well-differentiated adenocarcinoma, pT1a, N0, M0, pStage IA. No ICG-positive lymph nodes (8 nodes) contained metastases. Postoperative course was good, with no complications. Discussion: The use of VISION SENSE® allowing adjustment of excitation light and quantification of ICG fluorescence intensity might decreased the false-negative rate for SNs and increased the sensitivity of the ICG for detecting SNs. Conclusion: We successfully performed ICG SN mapping for early gastric cancer using VISION SENSE®.